2021
DOI: 10.1038/s41893-021-00809-0
|View full text |Cite
|
Sign up to set email alerts
|

Topologically protected oxygen redox in a layered manganese oxide cathode for sustainable batteries

Abstract: Manganese could be the element of choice for cathode materials used in large-scale energy storage systems owning to its abundance and low toxicity levels. However, both lithium and sodium ion batteries adopting this electrode chemistry suffer from rapid performance fading, suggesting a major technical barrier that must be overcome. Here we report a P3-type layered manganese oxide cathode Na 0.6 Li 0.2 Mn 0.8 O 2 (NLMO) that delivers a high capacity of 240 mAh g −1 with outstanding cycling stability in a lithiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 71 publications
0
63
2
Order By: Relevance
“…The degree of Ni/Li disorder is refined to 2.26% via the Rietveld‐refined XRD (Supporting Information: Table S1). The slight Ni Li antisites manifest as sporadic dark spots (yellow‐dotted circles) in the ABF STEM image (Figure 2E), suggesting the ordered Ni Li antisite ions along the [1true1¯ $\bar{1}$0] direction, as in the ribbon‐ordered superstructure of the TM layer in Na 0.6 Li 0.2 Mn 0.8 O 2 5 . The ribbon‐ordered Ni Li antisites gradually increase with the temperature rising from 100°C to 600°C (Supporting Information: Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The degree of Ni/Li disorder is refined to 2.26% via the Rietveld‐refined XRD (Supporting Information: Table S1). The slight Ni Li antisites manifest as sporadic dark spots (yellow‐dotted circles) in the ABF STEM image (Figure 2E), suggesting the ordered Ni Li antisite ions along the [1true1¯ $\bar{1}$0] direction, as in the ribbon‐ordered superstructure of the TM layer in Na 0.6 Li 0.2 Mn 0.8 O 2 5 . The ribbon‐ordered Ni Li antisites gradually increase with the temperature rising from 100°C to 600°C (Supporting Information: Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…). For example, Chen’s group found that Mg- and Ti-codoped Na 2/3 [Ni 2/9 Mg 1/9 Mn 5/9 Ti 1/9 ]­O 2 could regulate the crystal structure and enhance the electrochemical properties by suppressing the phase transition . Especially, when weak bonds like Li–O, Mg–O, or Zn–O bonds are introduced in the Na-deficient oxides, the anionic redox reaction O 2– /O n – could be triggered at a high working potential of around 4.2 V, which opens a new path to improve the specific capacity of these oxides. Na 2/3 [Mg 0.28 Mn 0.72 ]­O 2 is reported to have a high initial charge/discharge capacity of above 150 mAh g –1 due to the contribution of the O redox process, which is close to its theoretical capacity based on the Na content of the compound. Similar cases were encountered in Na 0.6 Li 0.2 Mn 0.8 O 2 and Na 2/3 Zn 0.28 Mn 0.72 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a Li-ion system, Na-ion layered oxides with P-type stacking can not only disfavor out-of-plane transition-metal (TM) migration but also provide ample void space to mediate the covalent bonding rearrangements upon LOR by virtue of the size mismatch between TM ions and prismatic Na sites, making them a more appropriate model system to harness the LOR activity. P-type Na-ion layered oxides mainly comprise P2 and P3, in which the oxygen columns demonstrate “ABBA” and “ABBCCA” arrangements along the [001] direction, respectively (as delineated in Figure ). Recently, Hu and co-workers proposed that the topological character of -α-γ- stacks in P3-Na 0.6 Li 0.2 Mn 0.8 O 2 can provide unexpected protection for reversible LOR, while the topological character of P2-Na 0.6 Li 0.2 Mn 0.8 O 2 evolves from -α-β- to -α-γ- stacks as cycling progresses, which jeopardizes the reversibility of LOR . In addition to the interlayer stacks, endeavors have also been dedicated to the design of intralayer atom configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hu and co-workers proposed that the topological character of -α-γ-stacks in P3-Na 0.6 Li 0.2 Mn 0.8 O 2 can provide unexpected protection for reversible LOR, while the topological character of P2-Na 0.6 Li 0.2 Mn 0.8 O 2 evolves from -α-β-to -α-γ-stacks as cycling progresses, which jeopardizes the reversibility of LOR. 30 In addition to the interlayer stacks, endeavors have also been dedicated to the design of intralayer atom configurations. For instance, Bruce et al first reported that the voltage hysteresis can be largely reduced in LORactive materials through a ribbon-ordered superstructure that precludes the in-plane migration of TM ions.…”
Section: ■ Introductionmentioning
confidence: 99%